Quality of Regional Financial Statements: The Influence of Information Systems on Financial Management and Fixed Assets Management - Dhea Perdana Coenraad; Rahmahwati Rahmahwati (Kontigensi : Jurnal Ilmiah Manajemen, 2020)
The purpose of this study was to determine the effect of regional financial management information systems and regional fixed asset management on the quality of local government financial reports either partially or simultaneously. The sampling technique in this research is using Probability Sampling with the Cluster sampling method. The sampling technique in this research is using Probability Sampling with the Cluster sampling method. Data collection was carried out by distributing questionnaires to 60 employees who perform accounting and financial administration functions in two local government agencies in West Bandung Regency. The collected data is processed using quantitative testing with regression analysis techniques. Hypothesis testing used is multiple linear regression analysis, t-test, F test, and determination coefficient. This study indicates that there is a positive effect partially and simultaneously between the regional financial management information system and regional fixed asset management on the quality of the report. The magnitude of the influence of the regional financial management information system and regional fixed asset management on local government financial reports' quality was 75.3%. In comparison, the remaining 24.7% influenced by other factors outside the variables studied. The recommendations recommended can further improve the performance of regional fixed asset management and improve the regional financial management information system's infrastructure.